The application of electrospun biofunctional scaffolds for stem cell differentiation and nerve regeneration - Jiang, Xu (2015)
Tissue engineering is a promising strategy with great therapeutic potential intended to assist the nerve regeneration. In addition to basic research on organ transplantation, some researches focus on creating an artificial environment enabling cells to induce tissue regeneration. To best mimic extracellular-matrix (ECM), ideal scaffolds can not only supply mechanical support for cell growth, but also regulate the functions of various cellular activities. Electrospun fibrous scaffolds serve as ideal biomimetic scaffolds due to their unique physical properties that closely resemble that of the ECM. Electrospun fibrous scaffolds can be prepared with controlled structure, and are amenable to various functional modifications targeted towards enhancing stem cell survival and proliferation, directing specific stem cell fates, or promoting tissue organization. In addition, signaling molecules can be incorporated into electrospun fibers in a spatially defined manner and enables the manipulation of cellular behaviors for specific applications. Accordingly, the aim of this thesis is to develop biomimetic scaffolds capable of delivering topographical and biochemical signals to enhance tissue regeneration via electrospinning; and to understand the phenotypic changes of cells interacting with such biofunctional scaffolds. In our works, we firstly demonstrated the combined effects of nanofiber topography and controlled drug release on enhancing MSC neural commitment. A scaffold-based drug delivery system was developed by encapsulating retinoic acid (RA) within aligned poly(ε-caprolactone) (PCL) nanofibers. A sustained released of retinoic acid was obtained for at least 14 days. Topographical cues presented by the electrospun fibers have profound impact on modulating cellular behaviors such as attachment, proliferation and differentiation. Compared with TCPS, nanofiber topography from aligned PCL nanofibers significantly up-regulated the expressions of neural markers at mRNA and protein levels. The synergistic effects of nanofiber topography and retinoic acid further enhanced the potential of MSCs to undergo neural differentiation. Despite lower totally amount of RA, scaffold-based controlled delivery of retinoic acid showed more significant enhancement in neural markers expressions and further enhanced MSCs neural differentiation, as compared to bolus delivery. The results highlight the advantage of the scaffold-based approach in enhancing the potential of MSC neuronal differentiation and demonstrated the importance of drug delivery approach in directing cell fate. Meanwhile, we also developed a polysaccharide scaffold that can provide combined substrate topography and matrix compliance signals to direct cell fate. Pullulan/dextran (P/D) nanofibers were fabricated with variable stiffness by in-situ crosslinking during electrospinning. Human first trimester mesenchymal stem cells (fMSCs) cultured on STMP14 P/D scaffolds (Young’s modulus: 7.84 kPa) in serum-free neuronal differentiation medium exhibited greatest extent of differentiation. It highlights the combined effects of substrate topography and matrix compliance signals in enhancing the probability of fMSC motor neural commitment and may help us understand the influence of topography and matrix stiffness on fMSC differentiation. Finally, we evaluated the feasibility of implanting the electrospun scaffolds in vivo and demonstrated the effects of substrate topography on nerve regeneration in vivo. Electrospun PCL conduits were used for peripheral nerve regeneration across a 15-mm critical defect gap in a rat sciatic nerve injury model. At three months post implantation, conduits with nanofiber topography (Nanofiber) resulted in significantly higher total number of myelinated axons and thicker myelin sheaths as compared to conduits with microfiber and flat topography (Microfiber and Film). Retrograde labeling also revealed a better nerve regeneration in the presence of Nanofiber conduits. In addition, motor-evoked responses showed better electrophysiological recovery in the Nanofiber conduit group as compared to the Microfiber group. Altogether, this study will help deepen the knowledge on basic cell biology involving fibrous scaffolds and broaden the application of fibrous scaffolds to general tissue engineering and neural regenerative medicine.